2014
DOI: 10.1371/journal.pone.0089811
|View full text |Cite
|
Sign up to set email alerts
|

2, 3, 7, 8-Tetrachlorodibenzo-P-Dioxin (TCDD) Induces Premature Senescence in Human and Rodent Neuronal Cells via ROS-Dependent Mechanisms

Abstract: The widespread environmental pollutant 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) is a potent toxicant that causes significant neurotoxicity. However, the biological events that participate in this process remain largely elusive. In the present study, we demonstrated that TCDD exposure triggered apparent premature senescence in rat pheochromocytoma (PC12) and human neuroblastoma SH-SY5Y cells. Senescence-associated β-galactosidase (SA-β-Gal) assay revealed that TCDD induced senescence in PC12 neuronal cells at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 50 publications
3
35
1
Order By: Relevance
“…Many studies implicated a role of the mitochondria disorder in TCDD-induced ROS generation (Aly and Khafagy, 2011;Ilavarasi et al, 2011). In line with the reports, our recent finding also indicated that TCDD could trigger ROS accumulation and oxidative stress to cause premature senescence in neuronal cells (Wan et al, 2014). Because the activation of WNT/β-catenin signaling has been documented to lead to potent mitochondrial ROS production, we proposed that WNT/β-catenin activation might be partially responsible for TCDD-induced ROS generation in astrocytes.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Many studies implicated a role of the mitochondria disorder in TCDD-induced ROS generation (Aly and Khafagy, 2011;Ilavarasi et al, 2011). In line with the reports, our recent finding also indicated that TCDD could trigger ROS accumulation and oxidative stress to cause premature senescence in neuronal cells (Wan et al, 2014). Because the activation of WNT/β-catenin signaling has been documented to lead to potent mitochondrial ROS production, we proposed that WNT/β-catenin activation might be partially responsible for TCDD-induced ROS generation in astrocytes.…”
Section: Discussionsupporting
confidence: 86%
“…Coinciding with the notion, ROS have been reported to be crucial mediators of astrocyte senescence under different stressful conditions (Bitto et al, 2010;Liu et al, 2011). In addition, because ROS are involved in mitochondrial dysfunction, changes in mitochondrial biogenesis may also contribute to TCDD-induced premature senescence (Wan et al, 2014). DNA damage is considered of paramount importance in senescence (Barja and Herrero, 2000;Liu et al, 2007;Yoon et al, 2010).…”
Section: Discussionmentioning
confidence: 91%
“…Reactive oxygen species (ROS) formation and subsequent peroxidation of membrane lipids, being mainly involved in TCDD toxicity, and the potency of OO and TY in eliminating the ROS and lipid peroxidation products so formed and protecting the PBMC were quantified. Being no exception to previous reports, TCDD significantly enhanced ROS formation and lipid peroxidation in PBMC (Wan et al 2014) (Figure 1). OO and TY, as reported earlier to protect cells from the toxicity of ROS produced due to the stimulus with various toxins and stresses, also protected PBMC from TCDD-induced ROS production and showed a marked decrease in the level of thiobarbituric acid reactive substances (TBARS) (measure of lipid peroxidation) and protected the subsequent destruction of cells.…”
Section: Resultscontrasting
confidence: 72%
“…1C and D). Such decreases in activity of intracellular dehydrogenases enzyme might increase the accumulation of cellular reactive oxygen species, decreasing the cell viability [34]. However, even in this case, it is obvious that the ITE-decreased activity of mitochondrial dehydrogenases in HUVECs is not sufficient to suppress migration of HUVECs.…”
Section: Discussionmentioning
confidence: 99%